Would Tirofiban Have Been Shown Non-Inferior to Abciximab Had the TENACITY Trial Not Been Terminated for Financial Reasons? - Berger, Peter B. (2013)
OBJECTIVES: To investigate whether tirofiban would have been non-inferior to abciximab had the trial completed enrollment, and we place the termination of this trial in a broader research ethics context. BACKGROUND: TENACITY was terminated by the sponsor for financial reasons. At the time, event rates for the 2 treatment arms were unknown. METHODS: TENACITY was designed to compare tirofiban with abciximab in approximately 8000 patients; however, enrollment was terminated after 383 (4.8%) patients. The primary endpoint was a composite of 30-day death, myocardial infarction, and urgent target vessel revascularization. Non-inferiority was defined as the likelihood that tirofiban would preserve at least 50% of the ability of abciximab to reduce the primary endpoint at 30 days, based on abciximab’s demonstrated ability to reduce such events by 43% (relative risk, 0.573; 95% confidence interval [CI], 0.507–0.648; P<0.001). To determine the probability of non-inferiority given the patients already enrolled, a Bayesian approach was used. RESULTS: The primary composite endpoint occurred in 8.8% of patients randomized to abciximab vs. 6.9% receiving high-bolus-dose tirofiban (odds ratio, 0.77; 95% CI, 0.37–1.64). The estimated conditional power for the test that tirofiban would be non-inferior to abciximab if all patients been enrolled is 93.7%. Using the estimated predictive power method, the likelihood was 84.8%. CONCLUSIONS: TENACITY was well-powered to identify non-inferiority with tirofiban vs. abciximab, and the patients enrolled strengthened the probability that this would have been the outcome had the trial been completed. When a clinical trial is terminated solely for financial reasons, it is incumbent upon the sponsor to provide proper patient follow-up and publication of the findings.